Uzbekistan Quality Job Creation as a Cornerstone for Sustainable Economic Growth: Country Diagnostic Study - K. Anderson; E. Ginting; K. Taniguchi (Asian Development Bank (ADB), 2020)
ADB analysis emphasizing the need for high-quality, productivity-enhancing jobs in Uzbekistan to sustain growth, improve social stability, and boost household welfare—supported by recent reform successes.